The Role of Career Path and Achievement Motivation in Organizational Sustainability from an Entrepreneurship Perspective - Gustiah, Indira Puspa; Siswanti, Indra; Kasmir, Kasmir; Nawangsari, Lenny Christina (Pandawan, 2025)
This study examines the effect of career path and achievement motivation on organizational sustainability, mediated by innovative work behavior and moderated by perceived organizational support. Participants were all indirect employees of an international manufacturing group in Japan, Australia, and Indonesia totaling 4462 employees, of whom 256 were selected. Data were collected using research instruments distributed to all employees in three languages using a back-translation system. Simple mediation and moderation regression analysis techniques using structural equation modeling with Partial Least Squares 3.0 program were used. The results indicate that CP, AM, and IWB have positive and significant effects on OS. IWB mediation had a positive and significant effect on the mediation of CP and AM on OS. The moderating effect of POS on IWB had a positive and significant effect on OS. The significance of moderation is clarified based on the slope analysis, in which the greater the POS toward IWB, the stronger the support for OS. The study is novel in its use of POS as a moderating variable. This study enriches the theoretical and practical implications of managing employees CP and AM toward OS.